2011
DOI: 10.1073/pnas.1109078108
|View full text |Cite
|
Sign up to set email alerts
|

Exoplasmic cysteine Cys384 of the HDL receptor SR-BI is critical for its sensitivity to a small-molecule inhibitor and normal lipid transport activity

Abstract: The HDL receptor, scavenger receptor, class B, type I (SR-BI), is a homooligomeric cell surface glycoprotein that controls HDL structure and metabolism by mediating the cellular selective uptake of lipids, mainly cholesteryl esters, from HDL. The mechanism underlying SR-BI-mediated lipid transfer, which differs from classic receptor-mediated endocytosis, involves a two-step process (binding followed by lipid transport) that is poorly understood. Our previous structure/activity analysis of the small-molecule in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(93 citation statements)
references
References 55 publications
8
84
0
Order By: Relevance
“…It has been effectively used to inhibit carotenoid uptake by SR-B1 (36,37,49) in intestinal cells and it does not inhibit other protein transporters (50). Interestingly, it has been found that BLT-1 inhibits cholesterol uptake by SR-B1 in a Cys384-dependent manner (51). BLT-1 attaches to Cys384, which is located in the lumen of the SR-B1 tunnel and blocks cholesterol transport.…”
Section: Discussionmentioning
confidence: 99%
“…It has been effectively used to inhibit carotenoid uptake by SR-B1 (36,37,49) in intestinal cells and it does not inhibit other protein transporters (50). Interestingly, it has been found that BLT-1 inhibits cholesterol uptake by SR-B1 in a Cys384-dependent manner (51). BLT-1 attaches to Cys384, which is located in the lumen of the SR-B1 tunnel and blocks cholesterol transport.…”
Section: Discussionmentioning
confidence: 99%
“…Blocker of lipid transport-1 (BLT-1) is a small molecule that binds cysteine-384 in the extracellular loop domain of SR-B1 and inhibits cholesterol flux through SR-B1 without altering the binding of HDL particles to the receptor (19). Thus, treatment of SUDHL-4 cells with BLT-1 allowed a measurement of engagement and cholesterol flux through SR-B1 (Materials and Methods).…”
Section: Inhibition Of Sr-b1 By Blocker Of Lipid Transport-1 Blocks Cmentioning
confidence: 99%
“…Uptake Experiment-The specific chemical inhibitor of SR-BI, BLT1, significantly decreased apical Caco-2 cell phylloquinone uptake by up to 38.5% when added at 50 nM (ϳIC 50 (28)). When added in excess (10 M (13, 15, 21, 25, 29)), it led to an inhibition of 84.5% of phylloquinone uptake (Fig.…”
Section: Involvement Of Sr-bi In Vitamin K 1 Transport Across the Apimentioning
confidence: 99%